Hypoglycemic Effect of Terminalia Chebula Retz. Fruit on Alloxan-Induced Diabetic Rats - Ei Pye Phyo Aung; Shin Hnaung Lwin; Nu Nu Aye; Khin Phyu Phyu (Siriraj Medical Journal, 2017)
Objective: To evaluate the hypoglycemic effect of ethanolic extract of terminalia chebula Retz. fruits on alloxan-induced diabetic rats compared with standard oral hypoglycemic drug, metformin. Methods: A randomized controlled experimental animal study was done. 30 Wistar albino rats were induced diabetes by alloxan (100 mg/kg). 80%-ethanolic extraction of fruits of terminalia chebula Retz. was performed by using Soxhlet extraction method. Group 1 was normal control. Group 2 was alloxan-induced diabetic control, group 3 was metformin 100 mg/kg standard group, groups 4, 5 and 6 were extracts 100, 200 and 400 mg/kg orally administered fruit extract for 28-days, respectively. Fasting blood glucose (FBG) levels were measured at the end of the first, second, third and fourth weeks by using standardized glucometer. Results: At the end of first, second, third and fourth weeks, the FBG levels of diabetic control were 325.7±28.2, 308.5±69.8, 322.7±65.8 and 369.2±57.4 mg/dL, those of metformin (100 mg/kg) were 76.2±9.5, 92.5±14.9, 94.5±17.9 and 90.8±9.9 mg/dL, those of the terminalia chebula Retz. extract 100 mg/kg were 232.5±78.6, 122.8±41.4, 109.2±33.6 and 132.3±41.1 mg/dL, extract 200 mg/kg were 82.7±8.2, 82.7±8.2, 89.7±9.8 and 89±15.2 mg/dL, and extract 400 mg/kg were 80.2±9, 83.5±7.1, 91±11.5 and 82.7±5.9 mg/dL, respectively. When all treatment groups were compared with diabetic control, the FBG levels were significantly reduced (p<0.001). There was no significant difference in FBG levels between standard group and extract (200 and 400 mg/kg) groups. Conclusion: The 80%-ethanolic extract of terminalia chebula Retz. has significant hypoglycemic effect on alloxan-induced diabetic rats and it was comparable with standard drug, metformin. The effective dose was 200 to 400 mg/kg.